An IoT-Based Smart Training Kit for Futsal Athlete Fitness Monitoring: Effectiveness and Perception - Rossi, Andriansyah; Achmad, Fendi; Zuhrie, M. Syariffudien; Wiyono , Agus (Edukasi, 2025)
This study aimed to evaluate the effectiveness and users perceptions of STARK (Smart Training Kit), an Internet of Things (IoT)-based device for monitoring the physical fitness of futsal athletes. The research adopted a Qualitative research design with descriptive apporach. The study was conducted at a futsal training center in Indonesia, involving ten athletes aged 17–25 years and one coach, selected through purposive sampling. Data collection tools included structured observation sheets, semi-structured interviews, and device-generated physiological data (heart rate and estimated VO₂ Max). Instruments were validated by sport science experts. Data were analyzed through descriptive qualitative techniques involving data reduction, thematic coding, and triangulation to ensure trustworthiness. The findings demonstrated that STARK effectively recorded real-time biometric data, showing an average heart rate increase of 86.42% post-training and an average estimated VO₂ Max of 43.76 ml/kg/min, indicating good aerobic fitness. Athletes and coaches reported high satisfaction with the device’s usability, accuracy, and training relevance. STARK also contributed to optimizing training load management and injury prevention. Despite limitations such as a small sample size and focus on limited physiological parameters, STARK offers a promising, user-friendly, and affordable solution for enhancing training quality in futsal. This study provides a foundation for future research on the broader application of IoT technology in sports science and practice.